STUDY OF SANITATIONFISH LANDING BASE PURNAMA URBAN VILLAGE DUMAI BARAT SUB-DISTRICT DUMAI CITY RIAU PROVINCE - Wandini, Ganda Ayu; Brown, Arthur; Zain, Jonny (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Sanitation is very important in the environment because it can affect health. The study was conducted during Maret 2019. This study was intended to formulate the actual sanitation conditions at Dumai Fish LandingBase. This study used a method of survey. The results of the research weretabulated into table form and analyzed descriptivelybased on scoring by respondents. The scoring were arrangeaccording to criteria that were determined onthat refer to national standards (52A/Kepmen-Kp/2013 and Agriculture Department).Based on the results of the research on sanitation conditions at Dumai Fish Landing Base wasquite good. Sanitation conditions is 1,7 with the range 1,50 – 1,99. The main cause of impurities atDumai Fish Landing Basewere food vendor around the port, buyers who littering, too many visitors at the port lack awareness to maintaining cleanliness, lack of availability of trash bins at the port and fish auction activities.Keywords : Sanitation, Dumai Fish Landing Base, Cleanliness